The Effect Of The Development Of Facilities And Services On The Level Of Customer Visits At Hotel De Baghraf Sumenep - Ahmadi, Dedy; Santoso, Fuji; Ainorrofiqie, Ainorrofiqie; Buhairi, Buhairi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Abstract—This study aims to find out and analyze the influence of the development of facilities and services on the level of customer visits at Hotel De Baghraf Sumenep. In the world of hospitality, the quality of facilities and services is an important factor that can influence customer decisions in choosing and visiting certain hotels, so a facility and service improvement strategy is needed to attract interest and increase customer satisfaction. This study uses a quantitative method with a descriptive approach. The data used was primary data obtained from the distribution of questionnaires to customers of Hotel De Baghraf Sumenep as many as 40 respondents. The sampling technique in this study uses purposive sampling, which is a technique of determining samples based on certain criteria. The results of the study show that the research instruments used are valid and reliable. The data in this study is also distributed normally, so it is eligible for regression analysis. Based on the results of a simple linear regression analysis, it was found that the development of facilities and services had a positive and significant effect on the level of customer visits at Hotel De Baghraf Sumenep. Thus, it can be concluded that the development of facilities and services has an important role in increasing the level of customer visits. Therefore, the De Baghraf Sumenep Hotel is advised to continue to develop and improve facilities and services on an ongoing basis.